Enlightened Feudalism : Seigneurial Justice and Village Society in Eighteenth-Century Northern Burgundy - Hayhoe, Jeremy (Book collections on Project MUSE., 2008)
In 'Enlightened Feudalism', Jeremy Hayhoe demonstrates that these local institutions actually functioned with a degree of efficiency, professionalism, and attention to peasant concerns that few historians have appreciated. Set in Northern Burgundy, this study reveals how provincial administrative elites quietly encouraged the use of simpler procedure for minor disputes, thus bringing seigneurial courts closer to village life. But these reforms paradoxically made the newly invigorated courts a key instrument of the late eighteenth-century intensification of the seigneurie. Peasant ambivalence toward seigneurial courts reflected this duality, as the 'cahiers de doleances' both praised the institution for its role in community affairs, and vigorously criticized it for bolstering the seigneurial system. By situating the local court within a wide range of para-judicial institutions and behaviors, Hayhoe presents a new vision of village society, one in which communal bonds were too weak to enforce behavioral norms. Village communities had substantial authority over their own affairs, but required the frequent and active collaboration of the court to enforce the rules that they put into place. Jeremy Hayhoe is assistant professor at the Universite de Moncton, New Brunswick, Canada.